Multifaceted Criticisms of the Bhagavad Gītā - Khatri, Tilak Bahadur (Cognition, 2022)
This research article deals with the multi-dimensional commentaries of the Bhagavad Gītā given by some of the major commentators in the nineteenth century India. The study has its relevance to understand the text through multi-dimensional lens. The article addresses on the research problem concerning to the variant criticisms of the same text the Gītā. The research approach (methodology) adopted for this study is the review-based analysis of the text's commentaries of some of the well-known nineteenth century Indian commentators. The study has included the commentaries of Vivekananda, Gandhi, Desai, Aurobindo and Vinoba. The study reveals that the above commentators of the Gītā give the multilayered criticisms of the text, which are found to be queer and controversial.